Imaging Insights Into Abdominal Wall Function - Read, John W.; Ibrahim, Nabeel; Jacombs, Anita S. W.; Elstner, Kristen E.; Saunders, Jeni; Rodriguez-Acevedo, Omar (Frontiers in Surgery, 2022)
Purpose: Successful repair of complex abdominal wall hernias requires the surgeon to understand the patient’s disrupted abdominal wall anatomy; the size, location and characteristics of the abdominal wall defect(s); any contributing factors to the defect and why any previous repairs have failed. The adoption of a functional approach to CT imaging of the abdominal wall can provide this important information and also improve patient preparation and surgical planning. Methods: This invited article reports the observational experience gained by the authors from the functional abdominal wall CT examinations of 200+ patients who underwent ventral hernia repair using pre-operative Botulinum toxin A (BTA) infiltration of the lateral oblique abdominal wall muscles. Results: A functional CT scan protocol which supplements standard resting supine images with additional straining images can significantly improve the diagnostic work-up of ventral hernias and help plan the most effective operative approach. Images acquired during simultaneous strong contraction of all abdominal muscles will optimally define any abnormal abdominal wall morphology in a great majority of cases and can differentiate true hernias from dysfunctional bulges. They also identify muscle denervation or atrophic changes and may reveal otherwise occult hernias that can be missed on resting images alone. Conclusion: A functional approach to CT imaging can provide the surgeon with a more holistic understanding of pertinent alterations to abdominal wall structure and function in patients with hernia defects. Optimised scan technique and appropriate image post-processing can provide information that is invaluable to the formulation of effective surgical plans that achieve low recurrence rates and good functional outcomes.